'All you need is... entrepreneurial attitudes': a deeper look into the propensity to start a business during the COVID-19 through a gender comparison (GEM data). (4th February 2022) - Kariv, Dafna; Baldegger, Rico J.; Kashy-Rosenbaum, Gavriela
The COVID-19 captured entrepreneurs by surprise, and shocked in the first months of the pandemic, especially women entrepreneurs; yet, the initial stages of the 'shock' that crises induce, are still underexplored in the entrepreneurial research, though critical for the further venture creation act. The genders' perceptions of opportunity, fear of failure and motivations before and during the pandemic, are employed to predict propensity to start a business during this crisis. Results comparing the Global Entrepreneurship Monitor (GEM) datasets between 2019 and 2020 suggest that while pandemic has been found to affect women more severely than men, women's perceived availability of opportunities during COVID-19 emerged more tightly related to financial motivations, as their main impetus to start a business. These findings reinforce the relevance of the theory of planned behaviour and bricolage to the contexts of gender and crises. Implications for research and practice are discussed.